Professional baseball pitchers produce similar ball velocity and kinematics when pitching from the wind-up and stretch deliveries: a biomechanical analysis - Hodakowski, A.; Dowling, B.; Brusalis, C. M.; Olmanson, B. A.; Streepy, J. T.; McCormick, J. R.; Dowling, B. A.; Verma, N. N.; Garrigues, G. E. (Sports Biomechanics, 2024)
Historically, the wind-up delivery is considered a more biomechanically advantageous pitching motion compared to the stretch. Recently, some pitchers have shifted to pitching exclusively from the stretch regardless of the game situation. The goal of this study was to compare temporal, kinematic and kinetic variables between the wind-up and stretch deliveries. Professional pitchers (n = 52, 189.1 ± 4.8 cm, 92.8 ± 8.4 kg) threw fastballs evaluated by 3D-motion capture (480 Hz) from both the wind-up and stretch deliveries. Within a pitcher, there was no significant difference in ball velocity between the two deliveries (p = 0.15). The stretch delivery was significantly quicker to ball release at toe off 2 (p < 0.001) (the last frame the pitcher`s foot contacts the ground before progressing to maximum knee height) and maximum knee height (p < 0.001). The majority of differences occurred prior to foot contact. The wind-up delivery produced greater maximum shoulder external rotation (p < 0.001) and lead knee flexion at ball release (p < 0.001). Pitching from the stretch incurred greater shoulder superior force (p < 0.001). It remains unknown if this is clinically significant as pooled means show only a 2% difference. Therefore, pitching a fastball from either the wind-up or stretch delivery provides comparable mechanics and throwing arm load with likely comparable risk of injury.